Vocational Rehabilitation Counseling for Young Adults Recovering from Internet Gaming Disorder: A Career Guidance Approach - Zainatus Salma Al Qolbi (Asesment : Journal Of Counseling Guidance, 2024)
Background: Internet Gaming Disorder (IGD) significantly impairs vocational functioning in young adults, disrupting career development during critical establishment periods. Despite IGD's recognized clinical significance, vocational rehabilitation remains neglected in symptom-focused treatment approaches, creating a critical gap in comprehensive care for affected individuals.Objective: This study examines the effectiveness of vocational rehabilitation counseling using career guidance approaches for young adults recovering from IGD.Method: Twelve participants aged 21-28 years completed a structured 12-session intervention encompassing career assessment, skill mapping, graduated work exposure, and recovery integration. Data collection included validated career assessments, session documentation, semi-structured interviews, and six-month follow-ups, analyzed through within-case and cross-case thematic synthesis.Findings and Implications: Five interconnected domains emerged from the analysis: vocational identity reconstruction, skill recognition and confidence building, graduated exposure and behavioral activation, recovery-career integration, and social-environmental facilitation. Participants demonstrated substantial improvements in career decision-making self-efficacy, vocational identity clarity, and work readiness, with 75% maintaining gains at six-month follow-up and nearly half achieving employment or educational enrollment. These findings suggest that integrated vocational rehabilitation addressing both career development and recovery maintenance produces meaningful functional outcomes while supporting sustained recovery.Conclusion: This research establishes vocational rehabilitation as an essential component of comprehensive IGD treatment. The findings inform clinical practice, program development, and policy initiatives supporting young adults' successful transition to productive occupational roles, highlighting the necessity of incorporating vocational dimensions into standard IGD intervention frameworks.